Evolution of Gravimetric Glaciology: Revealing the Mysteries of Earth’s Freezing Giants - Geetha, P (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2024)
Gravimetric glaciology, the study of ice mass variations through gravity measurements, has emerged as a pivotal field in understanding the dynamics of glaciers and ice sheets. This review delves into recent advancements in gravimetric techniques, shedding light on their applications, challenges, and contributions to our understanding of cryospheric processes. From satellite missions like GRACE (Gravity Recovery and Climate Experiment) to ground-based gravimeters and airborne surveys, a myriad of instruments offer diverse perspectives on ice mass changes. These observations not only reveal the rapid thinning of glaciers and ice sheets but also provide crucial insights into their contributions to sea level rise. This review highlights the interdisciplinary nature of gravimetric glaciology and emphasizes the need for continued innovation to address the challenges posed by a changing climate. By synthesizing recent developments and future directions, this article aims to inspire further research in unraveling the secrets of Earth’s frozen giants.